Perceptions of Students and Lecturers on Project-Based Learning in Higher Education - Minarni Minarni; Rayandra Asyhar; Haryanto Haryanto; Bambang Hariyadi (Jurnal Penelitian Pendidikan IPA, 2025)
This study examines the perceptions of students and lecturers on Project-Based Learning (PjBL) in environmental chemistry courses at Jambi University, Indonesia, to evaluate its effectiveness and challenges. A mixed-method survey was conducted with 30 students and 30 lecturers using Likert-scale questionnaires and open-ended questions. Data were analyzed descriptively and thematically. All lecturers (100%) adopted PjBL, but only 46.67% published student outcomes. Meanwhile, 78% of students reported improved problem-solving skills, though 40% struggled with theory-practice linkages. While PjBL enhances engagement and skills, gaps in guidance (only 63.33% of lecturers provided written guidelines) and institutional support hinder optimal implementation. PjBL is effective but requires structured frameworks and resource allocation to address time constraints and material complexity in Indonesian higher education